2006
DOI: 10.1107/s160053680603217x
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl 4-(4-isopropylcarbonyloxyphenyl)-2,6-dimethyl-1,4-dihydropyridine-3,5-dicarboxylate

Abstract: Key indicatorsSingle-crystal X-ray study T = 273 K Mean (C-C) = 0.002 Å Disorder in main residue R factor = 0.049 wR factor = 0.141 Data-to-parameter ratio = 13.1 For details of how these key indicators were automatically derived from the article, see

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 7 publications
2
3
0
Order By: Relevance
“…1 shows the molecular structure of (I) with the atomic numbering scheme. The bond lengths and angles of the 1,4-DHP ring (Table 1) are comparable with those reported for similar structures Sundar, Parthasarathi, Narang et al, 2006). The substituted 1,4-DHP ring has a flattened-boat conformation [puckering parameters (Cremer & Pople, 1975) Q = 0.342 (2) A ˚, q 2 = 0.329 (2) A ˚, q 3 = 0.096 (2) A ˚, = 73.7 (3) and ' = 180.7 (3) for the atom sequence N1/C2/C3/C4/C5/C6].…”
Section: Commentsupporting
confidence: 84%
See 1 more Smart Citation
“…1 shows the molecular structure of (I) with the atomic numbering scheme. The bond lengths and angles of the 1,4-DHP ring (Table 1) are comparable with those reported for similar structures Sundar, Parthasarathi, Narang et al, 2006). The substituted 1,4-DHP ring has a flattened-boat conformation [puckering parameters (Cremer & Pople, 1975) Q = 0.342 (2) A ˚, q 2 = 0.329 (2) A ˚, q 3 = 0.096 (2) A ˚, = 73.7 (3) and ' = 180.7 (3) for the atom sequence N1/C2/C3/C4/C5/C6].…”
Section: Commentsupporting
confidence: 84%
“…Compounds containing the 1,4-dihydropyridine (1,4-DHP) entity exhibit calcium-antagonistic activity and are prescribed as drugs in the treatment of a variety of cardiovascular disorders, such as angina and hypertension (Triggle et al, 1989). The present paper reports the structure and conformation of the title compound, (I), which was determined as a continuation of our investigation of a series of 1,4-DHP derivatives to determine the conformational changes due to different substituents effected at the 3-, 4-and 5-positions Sundar, Parthasarathi, Narang et al, 2006). Fig.…”
Section: Commentmentioning
confidence: 98%
“…1 shows the molecular structure of (I) with the atomic numbering scheme. The bond lengths and angles of the 1,4-DHP ring are comparable with those reported for similar structures Sundar, Parthasarathi, Narang et al, 2006;Sundar, Parthasarathi, Jain et al, 2006). The substituted 1,4-DHP ring adopts a flattened boat conformation [puckering parameters (Cremer & Pople, 1975) Q = 0.257 (2) Å , q 2 = 0.245 (2) Å , q 3 = 0.080 (2) Å , = 71.8 (4) and ' = 181.2 (5) for the atom sequence N1/C2/C3/C4/C5/C6].…”
Section: Commentsupporting
confidence: 85%
“…Compounds containing the 1,4-dihydropyridine (1,4-DHP) ring exhibit calcium-antagonistic activity and are prescribed as drugs in the treatment of a variety of cardiovascular diseases, such as angina and hypertension (Triggle et al, 1989). The present report of the title compound, (I), is part of a series of structural investigations of 1,4-DHP derivatives to determine the conformational changes due to different substituents at the 3-, 4-and 5-positions Sundar, Parthasarathi, Narang et al, 2006;Sundar, Parthasarathi, Jain et al, 2006). Fig.…”
Section: Commentmentioning
confidence: 99%
“…Considerable downfield shifting of the aromatic protons of the phenyl ring attached at 4‐position of dihydropyridine nucleus due to ester linkage was also observed. X‐ray crystallography studies of DHPs 9a and 9c were also carried out to further authenticate the structures and to study their three‐dimensional orientations [Sundar et al., ,b]. A literature survey has revealed that DHPs with an unsymmetrical ester substitution are, in general, more potent than symmetrically substituted derivatives due to a gain in bulk at the port side ester, which presumably interacts with a hydrophobic receptor domain [Mannhold, ].…”
Section: Resultsmentioning
confidence: 99%